THE POWER OF SOCIAL NETWORK CONSTRUCTION AND ANALYSIS FOR KNOWLEDGE DISCOVERY IN THE MEDICAL REFERRAL PROCESS - Almansoori, Wadhah; Addam, Omar; Zarour, Omar; Elzohbi, Mohamad; Sarhan, Abdullah; Kaya, Mehmet; Alhajj, Reda (Taylor & Francis Inc, 2014)
The social network model is powerful enough to provide for the analysis and study of a variety of application domains from daily life, including health care and health informatics. After the widespread appearance of automated tools capable of deriving and analyzing social networks, social network analysis (SNA) and mining in the health care domain has recently received considerable attention for its key role in understanding how various bodies within the health care system form communities and how they are socially connected with each other. This understanding helps enhance the organizational structures and process flows, among others. In this article, we show how SNA techniques can solve issues in the medical referral system in the Canadian health care system and the like, by analyzing the social network of general practitioners (GPs) and specialists (SPs). One of the main targets is to optimize the communication between GPs and SPs with hopes of decreasing the waiting time of patients to be seen by SPs. Various SNA and mining techniques are described and analyzed, backed by reporting some experimental results.
Keywords: social network analysis; medical referral system; communities; healthcare; health informatics